Modernization and socio-economic development of the Romanian rural area: 1995-2016 evolution - Lorena Florentina Chiṭea; Ion Dona (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
The present paper intends to establish a reciprocity relationship between the modernization and development level of the rural space, as main modernization-development point of the rural household. On the basis of the interdependence relation between rural area modernization and development, the paper aims to establish a typology of the modernization-development potential of rural areas from the socio-economic point of view, starting from the premise that there are significant differences between the rural areas. The starting point in establishing this reciprocity is the development of a theoretical model for the evaluation of the socio-economic modernization and development level of the rural space in terms of the modernization-development potential of the countryside. Having in view the concerns for a balanced economic and social development in the recent period as well as the multidimensional character of rural development, we have opted for a set of relevant indicators to reveal the socio-economic development level (in terms of economic performance and living standard) in the rural area across counties. In the paper, each social and economic indicator will be approached to reveal the gap between counties, and finally a hierarchy of counties according to the composite indicators will be established to capture the socio-economic modernization and development level of rural areas, as well as the interdependency between these two phenomena. The entire analysis will be made from the point of view of the main actor: the rural household.
Keywords: R20; Q01; O2; 330; rural area; rural household; sustainable development